2018
DOI: 10.1002/anie.201807317
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Same Reaction Monitored over Nine Orders of Magnitude in Concentration: When Are Unique Subensemble and Single‐Turnover Reactivity Displayed?

Abstract: Essentially no information is known about the behavior of individual molecular catalysts under reaction conditions. This is a result of the averaging inherent to traditional analytical techniques. Herein, a combined fluorescence microscopy and H NMR spectroscopy study reveals that unique (that is, non-ensemble averaged) distributions and time-variable kinetics from molecular ruthenium catalysts within growing polynorbornene occur and are detectable between 10 m and 10 m of substrate, surprisingly just 1000-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…We became interested whether single‐molecule/single‐turnover imaging techniques could address these analytical challenges [15–24] . We started our studies by designing a pair of fluorescent molecules that could differentiate between two different reaction pathways [25] in the living metathesis polymerization reaction at aggregate 1 (Figure 1 a).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…We became interested whether single‐molecule/single‐turnover imaging techniques could address these analytical challenges [15–24] . We started our studies by designing a pair of fluorescent molecules that could differentiate between two different reaction pathways [25] in the living metathesis polymerization reaction at aggregate 1 (Figure 1 a).…”
Section: Figurementioning
confidence: 99%
“…In this competition experiment, each single flash denotes the instantaneous chemoselectivity of a single catalyst. The low concentration of imaging agents and the high concentration of living strands within 1 means that each flash likely occurs at a different individual catalyst [16, 17, 26, 27] . Further, the high initial concentration of untagged norbornene (prior to precipitation of 1 and subsequent rinsing) and the low concentration of imaging agents 2 and 3 mean that most polymer is composed of untagged (dark) norbornene.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…9 Exquisite detail regarding catalyst turnover has been elucidated using techniques such as heteronuclear NMR magnetisation transfer, 10 dynamic nuclear polarisation labelling, 11 and single-molecule uorescence. 12 However, much of the work in the primary phases of the development of new ruthenium precatalysts, and the investigation of their relative efficiency and activity, focussed on the initiation event. 1,4,5 A now classic example of such initiation studies is the series of experiments reported by Grubbs, Sanford and Love et al in which a large excess of ethyl vinyl ether (EVE) was used to generate styrene and a stable Fischertype alkylidene product [Ru] ¼ CHOEt, in an apparently irreversible manner.…”
Section: Initiation In Metathesismentioning
confidence: 99%
“…Over the last decade, single‐molecule fluorescence spectroscopy (SMFS) emerged as a tool to bring insights into the microscopic behavior of molecular, chemical systems . When ensemble measurements conceal uncommon events, single‐molecule observation has the potential to provide a deeper understanding of chemical processes . In these first studies, it was shown that even text book reactions can show furcations of reaction pathways, still leading to an identical product .…”
Section: Introductionmentioning
confidence: 99%